2018
DOI: 10.1177/2050157917747642
|View full text |Cite
|
Sign up to set email alerts
|

Video-ethnography of social media apps’ connection cues in public settings

Abstract: This paper aims to analyze the uses of mobile social network services (mSNS) during daily commutes on the basis of a video ethnography conducted with 35 users of the Facebook app. This method is based on the combination of context-oriented recordings made with user-worn camera glasses and mobile screen video capture. These data reveal the way smartphone usage patterns tend to be organized according to notification functions (mSNS, SMS), a specific set of technical cues that mediatize social demand and promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Such studies provide insights into our understanding of the psychological implications of using mobile technology while on-the-go. In terms of affect, usage of mobile technology is often driven by boredom, but perhaps more so while on-the-go due to the lack of available alternatives (Figeac & Chaulet, 2018). Furthermore, Reichow and Friemel (2020) argued that perceived insecurity is more likely on public transportation, and users may utilize mobile technology to create a sense of social presence that dispels insecurity.…”
Section: Using Mobile Technology On-the-gomentioning
confidence: 99%
“…Such studies provide insights into our understanding of the psychological implications of using mobile technology while on-the-go. In terms of affect, usage of mobile technology is often driven by boredom, but perhaps more so while on-the-go due to the lack of available alternatives (Figeac & Chaulet, 2018). Furthermore, Reichow and Friemel (2020) argued that perceived insecurity is more likely on public transportation, and users may utilize mobile technology to create a sense of social presence that dispels insecurity.…”
Section: Using Mobile Technology On-the-gomentioning
confidence: 99%
“…Figeac and Chaulet (2018) present a video-ethnography of social media use, where they use a setup including both camera glasses and screen recordings of the participants’ mobile phone screen. In this way, they were able to approach how participants organized their social media activities in relation to the spatial and temporal constraints of the local setting, in their case being public transportation.…”
Section: Studying Selfies In the Fieldmentioning
confidence: 99%
“…These examples show how selfie photographers orient to the local setting at the same time as they are involved in selfie exchanges, and that selfie-taking is both spatially and temporally organized. Figeac and Chaulet (2018) showed how their study participants would draw upon certain technologically designed activity breaks, such as loading times, to look around, in this way monitoring the surroundings and managing their mobility. Using our ethnographic techniques it is difficult to capture the full situation, but we still get a sense of the embeddedness and situatedness of selfie photography.…”
Section: Selfies As Conversationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study of using public transport found gaze shifts away from the phone to be organized in relation to the sequential progression of the activity with the device. Beginning stages of phone use were suggested to be especially sequentially engaging but the methodology used and the level of granularity of the analyzes lacked the possibility to describe the interactive practices of in their sequential contexts [22].…”
Section: Introductionmentioning
confidence: 99%